Partisipasi Ibu dalam Bidang Ekonomi terhadap Keberhasilan Pemberian ASI Eksklusif di Indonesia - Agustina Kurniasih (CV. Syntax Corporation Indonesia, 2020)
Introduction: Breastfeeding is a mandate from God to mothers for their children because of the enormous benefits for the survival and development of children in the future. This study aims to determine the participation of mothers in the family economy towards exclusive breastfeeding. Method: This study is a further analysis of the 2017 IDHS data, with a sample of 13,636 mothers aged 15-49 who have babies aged 0-6 months. Data were analyzed using multiple logistic regression tests and processed with SPSS version 24. Results: Participation of mothers in the family economy can increase the chance of exclusive breastfeeding, where working mothers have a 1.6 times chance to give exclusive breastfeeding to their babies (p = 0,000; 95% CI = 1,420-1,707) compared to mothers who do not work. Conclusion: Women's participation in the economy has a significant relationship with exclusive breastfeeding. Specific support such as breaks for breastfeeding or milking, special room for breastfeeding and information about lactation management and personal support from colleagues or superiors are needed by working mothers to increase motivation for breastfeeding and maintain milk production